Pathways Through Which Green Exposure Type Influences Cardiovascular Diseases Mortality in Shanghai, China - Jianzhong HUANG; Yanting XU; Lan WANG; Zhouqian HE (Fengjing Yuanlin)
ObjectiveRapid urbanization has exacerbated traffic congestion, aggravated air and noise pollution, and limited public spaces, increasing the risk of suffering cardiovascular diseases (CVDs) such as hypertension and heart disease. Urban green spaces play a vital role in mitigating these risks by promoting mental restoration, reducing stress, encouraging outdoor exercise, improving air quality, and regulating temperature. The current research is identified with the following shortcomings despite the revealment of multiple positive health effects of urban green space. First, the research often focuses on single green exposure type, such as park accessibility or vegetation cover, overlooking the diverse pathways through which different green exposures influence cardiovascular health. Second, using streets or neighborhoods as research units can more comprehensively capture the group effect on health from people’s use of green space, and more specifically reveal the integrated effect of social interaction among residents, group behaviors and community public resources on health. Lastly, street-level analyses allow more precise environmental data integration, such as data on air pollution and temperature, which is often challenging in smaller individual-level units. Therefore, there is a need to conduct research on the influence of urban green exposure on CVDs mortality at the street level.MethodsThis research uses the partial least squares structural equation modeling (PLS-SEM) to analyze how different types of green exposure (vegetation cover, park accessibility, street green visibility, and park area per capita) influence cardiovascular disease mortality in 212 communities in Shanghai, China. The model incorporates three key mediating factors: Air pollution (measured by PM2.5 concentration), extreme high temperature, and physical activity level. Through this approach, the research examines both the direct and indirect effects of vegetation coverage, park accessibility, street greenery, and per capita park area on CVDs mortality. The research draws on diverse data sources to ensure robust analysis: CVDs mortality data provided by the Shanghai Municipal Center for Disease Control and Prevention, PM2.5 concentration data retrieved from MODIS satellite imaging, temperature data sourced from Google Earth Engine, and LBS (location based services) data serving as the basis for estimating physical activity levels. This comprehensive dataset allows for an in-depth exploration of the pathways through which green exposure influences cardiovascular health in an urban context.ResultsThe research finds that green exposure primarily influences CVDs mortality through physical activity levels, based on which a pathway of “green exposure − physical activity level − CVDs mortality” is established (pathway coefficient = －0.184, p < 0.05). Notably, direct associations between PM2.5 levels, extreme heat days, heat waves, and CVDs mortality are not statistically significant. Specifically, visibility of street greenery and vegetation coverage were shown to reduce CVDs mortality by promoting higher levels of physical activity among residents. Residential green spaces, “pocket parks” and street trees — due to their extensive reach, longer boundaries, and greater accessibility — encourage walking, cycling, and other active travel modes. This frequent, natural exposure to green spaces significantly enhances cardiovascular health by increasing both the duration and frequency of interaction with greenery, even surpassing the health benefits of larger centralized parks. The results indicate that smaller green spaces within residential areas and street greenery in densely populated and resource-limited areas are particularly effective in supporting cardiovascular health. In contrast, streets with a higher per capita green space show lower levels of physical activity, a trend attributed to their location on the urban fringe area, where park accessibility, green space quality, and safety are generally lower. Additionally, building density, road density, and land-use mix emerge as direct predictors of CVDs mortality. Building density, in particular, can indirectly influence the influence of green exposure on CVDs mortality by modulating physical activity levels as a mediating factor.ConclusionThis research offers an in-depth analysis of the complex mechanisms by which various types of green exposure influence CVDs mortality, with a particular focus on the key mediating role of physical activity. Findings suggest that increasing street greenery, vegetation coverage, and per capita park area can significantly enhance residents’ physical activity levels, which in turn helps lower CVDs mortality. However, the research does not find significant mediating effects of air pollution or heat waves, and the potential of green spaces to improve air quality remains relevant. These findings contribute valuable insights to the theoretical understanding of how green exposure influences chronic non-communicable diseases and provide critical scientific support for urban planning and public health policies. In practice, urban planners should holistically consider the integration of diverse types of green spaces to maximize their benefits for cardiovascular health, thereby supporting the broader well-being of urban populations.